PENGARUH KOMPETENSI GURU DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR ILMU PENGETAHUAN SOSIAL - Nurul Hardian Larasati (Herodotus: Jurnal Pendidikan IPS, 2018)
This study was to determine the effect of teacher competence and learning motivation on student learning achievement in social studies subjects. If indeed there is a positive and significant influence, then how strong is the influence of teacher competence and learning motivation on social studies learning achievement. The research method used is a survey with correlation and regression analysis, which connects between data that shows the influence of interest and learning motivation on student achievement in social studies subjects. Data on teacher competency variables and learning motivation were obtained through questionnaires compiled by researchers, namely measuring things related to the two things above. While the data on social studies learning achievements are obtained through direct tests conducted by researchers towards respondents. Hypothesis test results show:1) There is a significant effect of teacher competency and learning motivation together on the social studies learning achievement of Private Middle School students in Sukamajaya District, Depok. This is evidenced by the acquisition of Sig. 0,000 <0,05 and Fh = 180,176) There is a significant effect of teacher competency on social studies learning achievement of private junior high school students in Sukamajaya District, Depok. This is evidenced by the results of hypothesis testing obtained that the Sig. 0,000 <0,05 and th = 15,280) There is a significant effect of learning motivation on social studies learning achievement of private junior high school students in Sukamajaya District, Depok. This is evidenced by the results of hypothesis testing obtained that the Sig. 0,000 <0,05 and th = 8,877.